Medication use for headaches and migraine in Iceland: A pilot for the SAGA cohort study - Karen Sigfúsdóttir 1990- (2015)
Aim: To examine medication use for headaches and migraine in Icelandic people and see whether there is an association between pain intensity and duration of attacks. Methods: Data from a pilot for the SAGA cohort study (2013-2014) was used in current study. Females were randomly selected from those who had agreed to participate in a nationwide cancer screening and the males were randomly selected from the National Register of Iceland. In total 2870 were invited to participate, 991 agreed to participate and of those 921 submitted questionnaires, 402 males and 519 females. Pain intensity, duration of headaches and medication use were compared in subjects with migraine without aura (MO), migraine with aura (MA) and non-migraine headache (NMH). Migraine diagnoses were determined in accordance with the International Headache Society (IHS) criteria of 2013. Appropriate statistical tests were used to compare medication use between headache groups. Results: The overall prevalence of migraine was 14.9 %, 19.7 % for females and 8.7 % for males. The prevalence of migraine decreased with age. Medication use was more frequent in subjects with MO than MA, and the use of over the counter drugs (OTC) was considerably higher than the use of prescription drugs. Higher pain intensity was associated with types of medication used, number of headache attacks and the likelihood of seeking medical care. Pain intensity of migraine was negatively associated with quality of life. Conclusions: Migraine prevalence is slightly higher than that reported in previous studies using IHS criteria. While female migraineurs report higher pain intensity than males, the degree to which migraine affects quality of life appears similar for males and females. Markmið: Markmið rannsóknarinnar var að skoða lyfjanotkun Íslendinga við höfuðverk og mígreni. Í framhaldi af því var ákveðið að kanna hvort samband væri milli lyfjanotkunar og hversu svæsnir verkirnir voru og lengd höfuverkjakasta. Aðferðir: Gögn úr forrannsókn Heilsusögu Íslendinga (2013-2014) ...